2022
DOI: 10.1155/2022/1466478
|View full text |Cite
|
Sign up to set email alerts
|

Knee Osteoarthritis: Kinesiophobia and Isometric Strength of Quadriceps in Women

Abstract: Introduction. Osteoarthritis is a disease characterized by progressive wear and tear of the joint, with the knee being the most affected region. These patients have reduced mobility and mobility, among other symptoms. Thus, it is necessary to know the variables that influence the ability to walk. Objective. To analyze how much the gait capacity, in the performance of the six-minute walk test, can be influenced by the maximum isometric strength of the quadriceps or by kinesiophobia in women with knee osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…diz OA'lı kadınlarda 6 dk yürüme testi performansında yürüme kapasitesinin kuadriseps femoris maksimum izometrik kuvveti veya kinezyofobiden ne kadar etkilenebileceğini analiz etmişlerdir. 23 Yürüme kapasitesinin kuadriseps kas kuvveti ile pozitif yönde, kinezyofobi ile negatif yönde ilişkili olduğunu bulmuşlardır. 23 Baert ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…diz OA'lı kadınlarda 6 dk yürüme testi performansında yürüme kapasitesinin kuadriseps femoris maksimum izometrik kuvveti veya kinezyofobiden ne kadar etkilenebileceğini analiz etmişlerdir. 23 Yürüme kapasitesinin kuadriseps kas kuvveti ile pozitif yönde, kinezyofobi ile negatif yönde ilişkili olduğunu bulmuşlardır. 23 Baert ve ark.…”
Section: Discussionunclassified
“…23 Yürüme kapasitesinin kuadriseps kas kuvveti ile pozitif yönde, kinezyofobi ile negatif yönde ilişkili olduğunu bulmuşlardır. 23 Baert ve ark. yaptıkları bir çalışmada, diz OA'lı bireylerde psikososyal faktörlerin, yani ağrı felaketleştirme, kinezyofobi ve uyumsuz başa çıkma stratejilerinin kas gücü, ağrı ve fiziksel performans ile ilişkisini incelemişlerdir.…”
Section: Discussionunclassified
“…Hence, even though animal models studied closely by Herzog and Longino revealed muscle weakness alone can independently increase the risk for joint degeneration processes that lead to osteoarthritis, and Yousef, et al, noted quadriceps muscle weakness did cause a state of increased degeneration of the retro-patellar cartilage of arthritic rabbits, this group implied future work is needed here to delineate whether muscle weakness directly affects joint degeneration, or if changes in function and movement execution associated with muscle weakness are responsible for the increased rate of the onset and progression of osteoarthritis [51,52]. Egloff, et al, noted that while muscle weakness can induce osteoarthritis, that may impact walking ability, it is also possible that it is the strength imbalance between the knee flexors and extensors of an affected leg in the later stages of the disease rather than knee extensor strength alone that can promote further wear of an already disrupted knee joint surface DOI: https://doi.org/10.46889/JOSR.2022.3307 [53][54][55]. Hence it is suggested that measures of both strength, and muscle co-activity assessed in parallel can probably provide additional information related to knee osteoarthritis and how to mitigate its progression and severity than failing to do this [56].…”
Section: Key Findingsmentioning
confidence: 99%
“…It is currently believed that age, gender, menopausal in uence, history of joint injury, obesity and joint instability, and repetitive motions are all risk factors for the occurrence of OA. And a recent survey showed that the incidence of knee OA in women over 60 years of age is twice as high as that in men of the same age [6][7][8][9][10][11][12][13] . Treatment of OA is categorized as either non-surgical or surgical treatment.…”
Section: Introductionmentioning
confidence: 99%